2018
DOI: 10.5194/acp-18-11739-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aerosol hygroscopicity, mixing state, and CCN activity at a suburban site in the central North China Plain

Abstract: Abstract. This study investigates aerosol hygroscopicity, mixing state, and cloud condensation nucleation as part of the Atmosphere–Aerosol–Boundary Layer–Cloud Interaction Joint Experiment performed in the summer of 2016 at Xingtai (XT), a suburban site located in the center of the North China Plain (NCP). In general, the probability density function (PDF) of the hygroscopicity parameter (κ) for 40–200 nm particles had a unimodal distribution, and mean κ-PDF patterns for different sizes were similar, suggesti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 58 publications
4
70
0
Order By: Relevance
“…The H‐TDMA system used in this study was custom built (Tan et al, ; Y. Wang, Li, et al, ). Briefly, this system mainly includes two differential mobility analyzers (DMA, model 3081L, TSI Inc.) and a water‐based condensation particle counter (WCPC, model 3787, TSI Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H‐TDMA system used in this study was custom built (Tan et al, ; Y. Wang, Li, et al, ). Briefly, this system mainly includes two differential mobility analyzers (DMA, model 3081L, TSI Inc.) and a water‐based condensation particle counter (WCPC, model 3787, TSI Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The H‐TDMA can measure the GF probability distribution function (GF‐PDF) for particles with a specified diameter. Detailed information on the aerosol hygroscopicity conveyed in the measurements of the H‐TDMA can be used to study aerosol sources (Y. Wang et al, ; Xie et al, ). This is because the GF‐PDF pattern depends on aerosol chemical composition and the mixing state, both of which are highly related to aerosol formation and aging processes (Liu et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The sampling site has a high aerosol background value (H. , which could cause a significant deviation in the counting rate of the DMT-CCNC owing to water depletion (Deng et al, 2011), making measured N CCN lower than actual N CCN (Wang et al, 2018). One end of the black carbon tube was extended out of the laboratory, and the other was connected to the instrument to measure the ambient atmosphere.…”
Section: Experimental Settingmentioning
confidence: 99%
“…In reality, the uncertainty of using the mean value of κ to estimate the CCN number concentration varies with atmospheric conditions. Most studies show that the uncertainty is within 10% (Deng et al, ; Jurányi et al, ; Wang et al, ). The hygroscopicity parameter κ describes the relationship between the particle dry diameter and CCN activity when compositional data are not available (Petters & Kreidenweis, ).…”
Section: Methodsmentioning
confidence: 99%
“…The hygroscopicity parameter κ describes the relationship between the particle dry diameter and CCN activity when compositional data are not available (Petters & Kreidenweis, ). Wang et al () found that the sensitivity of the estimated CCN concentration to κ depends strongly on the variability of the shape of the aerosol size distribution. The sensitivity of CCN concentration to κ becomes weaker with increasing supersaturations, suggesting that chemical composition becomes less important in CCN concentration estimates at larger supersaturations .…”
Section: Methodsmentioning
confidence: 99%